New integral inequalities for (s,m)- and ( α ,m)-preinvex functions - Meftah, Badreddine; Aouissi, Nassima (Revista MATUA, 2018)
In this note, we give some estimate of the left hand side of generalized quadrature formula of Gauss-Jacobi in the cases where f and |f| ^λ for λ >1, are ( s,m) - and ( α ,m) -preinvex functions.